ANALISIS KEAMANAN APLIKASI EMAIL BAWAAN ANDROID DAN GMAIL PADA JARINGAN NIRKABEL - Hamid Hamid (Faculty of Industrial Technology Universitas Islam Indonesia, 2017)
ARP Poisoning / ARP Spoofing and sniffing will always threaten wireless network user. The rise of android-based smartphone user and internet wireless network provider, allowing smartphone users to access anything including email from anywhere they want. This paper provides an overview of comparison of security analysis between use the embedded android email application with gmail email application that is connected to wireless network, as well as providing an overview of possible attack methods. This paper also provides solutions to prevent attacks from the vulnerability found.